Pengaruh Likuiditas, Leverage, Profitabilitas dan Ukuran Perusahaan terhadap Financial Distress pada Perusahaan Barang Konsumsi yang Terdaftar di BEI Tahun 2016-2020. - Friska Darnawaty Sitorus; Ferdinand Hernandy; Wensly Triskietanto; Audi Angela; Vanessa (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of the researcher's research is to study and analyze the effect of liquidity using proxies CR (Current Ratio), leverage using proxies DAR (Debt to Asset Ratio), profitability using proxies RoA (Return on Assets), and Firm size against Financial Distress that occurred in consumer goods companies listed on the IDX in the period 2016 - 2020. This research using Quantity Method. Quantity Method is a technique that utilizes mathematical models in the form of numbers. The population in the consumer goods company is 90 companies and is selected using purposive sampling. Then the number of samples used amounted to 34 companies. The results in the partial tests, the liquidity variable using proxy Cash Ratio has a positive impact and not significant to Financial Distress. Leverage using DAR and company size with the calculation of Ln Total Assets are partially insignificant and have no negative impact on Financial Distress. Meanwhile, profitability by using RoA is partially significant and has a positive impact on Financial Distress and simultaneous test results : Liquidity (CR), Leverage (DAR) , Profitability (RoA) , and Firm Size have a significant effect on Financial Distress in consumer goods companies listed on the IDX in the period 2016 – 2020.